2012
DOI: 10.1111/j.1365-2613.2012.00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of insulin signalling pathway IRS‐1/IRS‐2/AKT/mTOR and decrease of epithelial cell proliferation in the prostate of glucocorticoid‐treated rats

Abstract: Previous studies by our research group using a model of insulin resistance induced by dexamethasone (DEX) showed that in the rat ventral prostate there was epithelial and smooth muscle cell atrophy and there were also alterations in fibroblasts. Proteins of the insulin signalling pathway are known to be very important for cell proliferation and development. Thus, we investigated the insulin signalling pathway and epithelial proliferation in the rat ventral prostate in this model and correlated the findings wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…IRs are present in most mammalian cells, and insulin-IR binding results in the activation of several phosphorylation-dephosphorylation cascades (11). Autophosphorylation of the intracellular β-subunit of IRs activates tyrosine kinase, which catalyzes multiple IR substrate (IRS) protein phosphorylation (12). Disruption in IRS protein phosphorylation or impaired PI3K recruitment from the cytosol, which results in PI3K inactivation, causes insulin resistance, followed by diabetes (13).…”
mentioning
confidence: 99%
“…IRs are present in most mammalian cells, and insulin-IR binding results in the activation of several phosphorylation-dephosphorylation cascades (11). Autophosphorylation of the intracellular β-subunit of IRs activates tyrosine kinase, which catalyzes multiple IR substrate (IRS) protein phosphorylation (12). Disruption in IRS protein phosphorylation or impaired PI3K recruitment from the cytosol, which results in PI3K inactivation, causes insulin resistance, followed by diabetes (13).…”
mentioning
confidence: 99%
“…1, G-I; Fig. 2, G-I), we assessed UT temporal expression of the mammalian target of rapamycin (mTOR) and nerve growth factor (NGF), as these genes are reported to promote cell proliferation (22,35,72). As recent evidence supports a dependence of urothelial repair upon signal feedback between basal UT cells, the stromal cells that underlie them, and the sonic hedgehog (SHh) signaling pathway (69), we also examined temporal expression of SHh and its associated receptor patched 1 (Pct1) (40).…”
Section: Temporal Profile Of Ut Gene Expression In Dmmentioning
confidence: 99%
“…Costa et al . () showed that the reduction in inhibition rate in animals treated with GCs leads to a reduction in plasma concentration of AKT and mTOR, proteins involved in the regulation of cell growth and development.…”
Section: Discussionmentioning
confidence: 99%